1999
DOI: 10.1038/sj.jhh.1000852
|View full text |Cite
|
Sign up to set email alerts
|

Altered sodium perception in essential hypertensive patients following rapid volume expansion

Abstract: We investigated sodium and volume-dependent mechanisms in the modulation of adrenal and renal vascular responsiveness to angiotensin II in hypertensive (n = 9) and normal subjects (n ‫؍‬ 5) who demonstrated normal responses during steady-state salt balance (intact modulation). Adrenal and renal vascular responses to angiotensin II were assessed on four occasions. These studies were performed during steady-state high salt and low salt balance and later during non-steady state conditions, after acute volume expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Our results are qualitatively concordant with more recent investigations in humans and dogs which came to similar overall conclusions regarding the importance of the RAAS in the regulation of total body sodium (Singer et al 1991; Drummer et al 1992; Singer et al 1994; Andersen et al 1998; Conlin et al 1999; Andersen et al 2000; Bie & Sandgaard, 2000; Reinhardt & Seeliger, 2000; Sandgaard et al 2000). Taken together the results indicate that the initial natriuretic response may depend heavily on: (1) suppression of the RAAS, (2) the sodium status of the subjects, (3) the duration of infusion, and (4) the rate of infusion, but not on changes in blood pressure.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are qualitatively concordant with more recent investigations in humans and dogs which came to similar overall conclusions regarding the importance of the RAAS in the regulation of total body sodium (Singer et al 1991; Drummer et al 1992; Singer et al 1994; Andersen et al 1998; Conlin et al 1999; Andersen et al 2000; Bie & Sandgaard, 2000; Reinhardt & Seeliger, 2000; Sandgaard et al 2000). Taken together the results indicate that the initial natriuretic response may depend heavily on: (1) suppression of the RAAS, (2) the sodium status of the subjects, (3) the duration of infusion, and (4) the rate of infusion, but not on changes in blood pressure.…”
Section: Discussionsupporting
confidence: 93%
“…Hypertension has been positively correlated with thirst (Shailendra et al, 2011); it was reported to increase thirst perception (Stachenfeld, 2008), stimulate RAAS (Atlas, 2007) and alter sodium perception (Conlin et al, 1999). But H. sabdariffa consumption was reported to reduce plasma aldosterone level (Nwachukwu et al, 2015b) and exert antihypertensive action in humans (Herrea-Arellano et al, 2004;McKay et al, 2010).…”
Section: Discussionmentioning
confidence: 99%